Analisis Determinan Penghindaran Pajak di Indonesia - Kennardi Tanujaya; Erna Erna (Global Financial Accounting Journal, 2021)
The purpose of this research is to determine the factors that impact tax avoidance in Indonesia. The factors used in this research are profitability, leverage, firm size, capital intensity, proportion of independent commissioner, audit quality, and audit committee. Purposive sampling method used to determine the object of research. The object of research is all companies’ financial statements which listed on the Indonesia Stock Exchange period 2015-2019. A total of 210 companies were used as research samples for the effective tax rate measurement and 230 companies were used as research samples for the cash effective tax rate measurement. The results indicate that profitability, leverage, and firm size have a significant effect on tax avoidance measure by effective tax rate. Capital intensity, proportion of independent commissioner, audit quality, and audit committee have no significant effect. The results indicate that profitability, leverage, and proportion of independent commissioner have a significant effect on tax avoidance measure by cash effective tax rate while firm size, capital intensity, audit quality, and audit committee have no significant effect. Hence, the investor can consider risk of tax avoidance occurred in the Company that cause potential loss in the future through analysis from the financial ratio and the effectiveness of the corporate governance implemented.